GNSS interference monitoring and detection based on the Swedish CORS network SWEPOS - Abraha Kibrom Ebuy; Frisk Anders; Wiklund Peter (Journal of Geodetic Science, 2024)
The presence of Global Navigation Satellite System (GNSS) interference poses a significant risk to both GNSS and the infrastructures that depend on them. This article describes how an existing GNSS infrastructure, the Swedish Continuously Operating Reference Stations network SWEPOS with more than 500 stations, can be leveraged to control the quality of GNSS signals and to be able to detect interferences in GNSS and adjacent frequency bands. This study introduces a SWEPOS-based automatic system that effectively detects GNSS interference by examining the signal-to-noise ratio (SNR) of Global Positioning System, Globalnaya Navigatsionnaya Sputnikovaya Sistema, Galileo, and BeiDou frequency bands. By comparing the SNR of tracked satellites against historical data, the system detects radio frequency interference (RFI) by statistically characterizing the SNR of simultaneously tracked satellites. Furthermore, based on the SNR characteristics across satellites, the system distinguishes between RFI and non-RFI sources. The effectiveness of the detection system is demonstrated through both simulated signal interference waves and real-world interference events.